Electrodiagnostic Characteristics Suggestive of Muscle-Specific Kinase Myasthenia Gravis. Issue 3 (June 2022) - Skolka, Michael; Lamb, Christopher J.; Rubin, Devon I.; Klein, Christopher J.; Laughlin, Ruple S.
Abstract : Background and Objectives: Muscle-specific kinase (MuSK) antibody–positive myasthenia gravis (MuSK + MG) is a form of MG with bulbar-predominant symptoms often resistant to conventional treatments. Patients with MuSK + MG may have an electrodiagnostic (EDX) profile distinct from other MG. This study compares EDX features of MuSK + MG with acetylcholine receptor (AChR) antibody–positive MG (AChR + MG) to discern whether any unique EDX pattern exists that can aid in clinical diagnosis. Methods: From January 1, 2010, through December 31, 2020, all patients with MuSK + MG at our institution were identified and randomly matched to an AChR + MG cohort in a 1:2 ratio based on sex, age at onset, and subsequently Myasthenia Gravis Foundation of America (MGFA) clinical severity for a case-control study. Each patient's clinical profile, treatment, and EDX testing were summarized and analyzed. Results: Twenty-two patients with MuSK + MG (18 female) and 44 patients with AChR + MG were studied. The average symptom duration at presentation was shorter in the MuSK + MG group (4.7 years) compared with AChR + MG (10.9 years). Myotonic discharges were rare in both groups but more frequently observed in patients with MuSK + MG (10%) identified in 5 muscles in 2 patients compared with AChR + MG (2%) noted in only 1 muscle in 1 patient. Patients with MuSK + MG more often had myopathic appearing motor unit potentials (MUPs) (41% vs 30%) compared with AChR + MG. Myopathic appearing MUPs were found in milder cases of MuSK + MG (MGFA class I–IIB) compared with AChR + MG (MGFA Class IIB–V). Discussion: Patients with MuSK + MG may have a recognizable EDX profile from AchR + MG that includes (1) myotonic discharges, (2) greater occurrence of myopathic appearing MUPs in clinically mild disease, and (3) symptoms leading to earlier testing.